Conventional and inverse magnetocaloric effects in La(0.45)Sr(0.55)MnO(3) nanoparticles - COEY, JOHN; VENKATESAN, MUNUSWAMY (My University, 2011)
The magnetocaloric effect of La(0.45)Sr(0.55)MnO(3) nanoparticles was studied by dc magnetization measurements. A sample with mean particle size of about 140 nm exhibits both a conventional magnetocaloric effect around the Curie temperature (approximate to 295 K) and a large inverse magnetocaloric effect around the antiferromagnetic-ferromagnetic transition temperature (approximate to 200 K). The change of magnetic entropy increases monotonically with applied magnetic field and reaches the values of 5.51 J/kg K and - 2.35 J/kg K at 200 K and 295 K, respectively, in an applied field of 5 T. The antiferromagnetic-ferromagnetic transition is absent in a 36 nm size sample, which shows only a broad ferromagnetic transition around 340 K and a small change in magnetic entropy near room temperature. The results are discussed in terms of the entropy difference between the A-type antiferromagnetic ground state of La(0.45)Sr(0.55)MnO(3) and the low moment ferromagnetic state. By comparing the results obtained on nanoparticles and bulk La(0.45)Sr(0.55)MnO(3), one can conclude that the inverse magnetocaloric effect in a material showing the antiferromagnetic-ferromagnetic transition could be improved over a wide range of temperature by tuning the spin disorder in the antiferromagnetic state.
PUBLISHED
Keywords: Condensed matter physics; MANGANITES; Nanoscience & Materials